HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN POLA HIDUP SEHAT ANAK - Sri Palupi (LPMPP Universitas Negeri Yogyakarta, 2007)
This article is about a research aimed at finding out the correlationbetween parents' educational level and elementary schoolchildren's pattern of healthy living in Depok, Sleman, DaerahIstimewa Yogyakarta.The research population consisted of 1.600 parents of 5th gradestudents from 56 state elementary schools in Depok, Sleman, DaerahIstimewa Yogyakarta (DIY). As the research sample, 300 parentsfrom 9 public elementary schools were selected by usingproportional random sampling.The result of a descriptive analysis reveals that 86.3% ofelementary school children's pattern of healthy living in Depok,Sleman, DIY is categorized good and 42.7% of their fathers and38.3% of their mothers are senior high school graduates. The resultof a correlation analysis reveals a significant correlation betweenparents' educational level and state elementary school children'spattern of healthy living in Depok, Sleman, DIY.